Total phenolic content and antioxidant activities of binahong (Anredera cordifolia.) - Hari Susanti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Background: Binahong plants are reportedly containing polyphenols, flavonoids, and steroid compounds. The content of polyphenols and flavonoids plays an important role as antioxidants. Research using the method of FRAP (Ferric Reducing Ability of Power) indicates that the antioxidant content of the binahongleaves extract is 3.68 mmol/100 g in dried leaves. This study offers new proof of antioxidant activity of all the aerial part of binahong.Objective: This research aims to determine the total phenolic content from binahong extract and its ability as free radical scavenger using DPPH method.Methods: The plant used in this research is every part of plants on the ground. The binahong extract is obtained by a maceration method with various solvents (hexane, chloroform, and methanol). Total phenolic content in the extract is spectrophotometrically determined with the Folin Ciocalteu reagent. Antioxidant activity assay is performed in vitro by the method of DPPH, with Gallic acid as a comparator. ES50 parameter is determined from the linear regression equation between the concentration of extracts and % scavenging.Results: The results showed that the total phenolic content of hexane, chloroform and methanol extract of Binahong was 8.54 ± 0.49 GAE mg/g, 17.30 ± 0.47 GAE mg/g and 32.5 ± 1.11 GAE mg/g. Hexane extract, chloroform extract and methanol extract of Binahong have a free radical scavenger activity. The value of ES50 extracts of hexane, chloroform, methanol, and successive acid errors is 58.601 ± 2.533 µg/ml, 446.219 ± 2.268 µg/ml, 237.683 ± 13.373 µg/ml and 2.058 ± 0.002 µg/ml.Conclusion: The capability of the three of binahong extract as a free radicals DPPH scavenger were weaker than gallic acid.Background: Binahong plants are reportedly containing polyphenols, flavonoids, and steroid compounds. The content of polyphenols and flavonoids plays an important role as antioxidants. Research using the method of FRAP (Ferric Reducing Ability of Power) indicates that the antioxidant content of the binahongleaves extract is 3.68 mmol/100 g in dried leaves. This study offers new proof of antioxidant activity of all the aerial part of binahong.Objective: This research aims to determine the total phenolic content from binahong extract and its ability as free radical scavenger using DPPH method.Methods: The plant used in this research is every part of plants on the ground. The binahong extract is obtained by a maceration method with various solvents (hexane, chloroform, and methanol). Total phenolic content in the extract is spectrophotometrically determined with the Folin Ciocalteu reagent. Antioxidant activity assay is performed in vitro by the method of DPPH, with Gallic acid as a comparator. ES50 parameter is determined from the linear regression equation between the concentration of extracts and % scavenging.Results: The results showed that the total phenolic content of hexane, chloroform and methanol extract of Binahong was 8.54 ± 0.49 GAE mg/g, 17.30 ± 0.47 GAE mg/g and 32.5 ± 1.11 GAE mg/g. Hexane extract, chloroform extract and methanol extract of Binahong have a free radical scavenger activity. The value of ES50 extracts of hexane, chloroform, methanol, and successive acid errors is 58.601 ± 2.533 µg/ml, 446.219 ± 2.268 µg/ml, 237.683 ± 13.373 µg/ml and 2.058 ± 0.002 µg/ml.Conclusion: The capability of the three of binahong extract as a free radicals DPPH scavenger were weaker than gallic acid.